Single image dehazing using generative adversarial networks based on an attention mechanism. Issue 7 (3rd March 2022) - Ma, Yongli; Xu, Jindong; Jia, Fei; Yan, Weiqing; Liu, Zhaowei; Ni, Mengying
Abstract: Most existing image dehazing methods rely on the solution of the atmospheric scattering model or supervised learning based on paired images. However, owing to incomplete prior knowledge and the lack of paired hazy and haze‐free images of the same scenes as training samples, their performances for single image dehazing are unsatisfactory. Here, the authors present an unpaired image learning method based on the attention mechanism for single image dehazing problems. The method uses the constraint transfer learning ability and circulatory structure of CycleGAN to carry out an unsupervised image dehazing task for unpaired data. Considering the complexity of the haze distribution in actual imaging and human visual characteristics, the improved channel attention and domain attention mechanisms are integrated into the network to process different features and different regions non‐uniformly. The experimental results show that the proposed method achieves good results on both synthetic datasets and real hazy images.